Leaving, staying in and returning to the hometown: Couple's residential location choices at the time of family formation; Gehen, Bleiben und Zurückkommen zum Ort der Kindheit und Jugend: Wohnstandortwahl von Paaren zur Zeit der Familiengründung - Janna Albrecht; Joachim Scheiner (Raumforschung und Raumordnung / Spatial Research and Planning, 2022)
Couples' residential decisions are based on a large variety of factors including housing preferences, family and other social ties, socialisation and residential biography (e.g. earlier experience in the life course) and environmental factors (e.g. housing market, labour market). This study examines, firstly, to what extent people stay in, return to or leave their hometown (referred to as 'migration type'). We refer to the hometown as the place where most of childhood and adolescence is spent. Secondly, we study which conditions shape a person's migration type. We mainly focus on variables capturing elements of the residential biography and both partners' family ties and family socialisation. We focus on the residential choices made at the time of family formation, i.e. when the first child is born. We employ multinomial regression modelling and cross-tabulations, based on two generations in a sample of families who mostly live in the wider Ruhr area, born around 1931 (parents) and 1957 (adult children). We find that migration type is significantly affected by a combination of both partners' place of origin, both partners' parents' places of residence, the number of previous moves, level of education and hometown population size. We conclude that complex patterns of experience made over the life course, socialisation and gendered patterns are at work. These mechanisms should be kept in mind when policymakers develop strategies to attract (return) migrants. – – Wohnstandortentscheidungen von Paaren basieren auf einer Vielzahl von Faktoren. Dazu gehören ihre individuellen Wohnstandortpräferenzen, sozialen (insbesondere familiären) Bindungen, wohnbiografischen Erfahrungen und Sozialisation und die räumlichen Rahmenbedingungen. Dieser Beitrag geht der Frage nach, in welchem Maße Menschen den Ort der Kindheit und Jugend verlassen, an diesem Ort bleiben oder zu ihm zurückkehren. Zudem wird untersucht, wovon dieser Migrationstyp abhängt. Im Fokus stehen dabei Einflussgrößen, die Elemente der Wohnbiographie, der familiären Bindungen und der familiären Sozialisation beider Partner erfassen. Dies wird zum Zeitpunkt der Familiengründung betrachtet. Es wird ein Familiendatensatz, der hauptsächlich im Ruhrgebiet wohnende erwachsenen Kinder (geboren um 1957) und ihre Eltern (geboren um 1931) umfasst, mithilfe von Kreuztabellen sowie multinomialen Regressionsmodellen ausgewertet. Die Ergebnisse zeigen, dass der Migrationstyp signifikant von dem Ort der Kindheit und Jugend und dem Wohnort der Eltern beider Partner, der Anzahl vorheriger Umzüge, der Bildung und der Bevölkerungsgröße des Ortes der Kindheit und Jugend abhängt. Es lässt sich schlussfolgern, dass Erfahrungen aus dem Lebensverlauf, Sozialisation und Geschlechterunterschiede komplex zusammenwirken. Für die Planungspraxis, die sich mit Abwanderung und der Aktivierung von Rückwanderung beschäftigt, liefert der Beitrag wertvolle Hinweise.
Keywords: 710; residential choice; residential biography; intergenerational family ties; return migration; family formation; Wohnstandortentscheidung; Wohnbiographie; familiäre Bindungen; Rückwanderung; Familiengründung